(untitled) (Ekonomski vjesnik/Econviews - Review of Contemporary Business, Entrepreneurship and Economic Issues, 2016)
The importance of student sport activities within the structure of academic development is arguably significant. However, university sport is one of the elements of academic development that is not represented adequately as a research subject on a global scale in both scientific and professional environments alike. Along with the global growth of university level education based on the rise of student mobility across countries and continents, and the strong global ICT development, a new perspective on university sport can be observed and several implications analyzed. The focus of this paper is set on the communication capabilities of the internet as a digital medium that can be used as a means of fostering student sport and related activities while taking into account the characteristics and behavioral components of the student population. The primary research was conducted on a sample of students of Josip Juraj Strossmayer University of Osijek. The research provided several interesting implications on student behavior regarding the general information collection and consumption, as well as information about student sport activities on the university level. The paper provides a brief sport marketing literature review and suggests several important guidelines for further research. The assumption that the internet is a key element in the marketing potential of student sport was confirmed. Comparative analysis of digital marketing activities of benchmark universities has been conducted in order to determine suggestions on creating and/or improving digital marketing tools such as web site, social network presence and mobile application for reaching marketing potential of university sport. Keywords: Digital marketing, Sports marketing, University sports, Social media in sports, Sports mobile apps